2016
DOI: 10.1021/acs.analchem.6b00264
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Total Excitation–Emission Fluorescence Microscopy Combined with Multi-Way Chemometric Analysis for Visually Indistinguishable Single Fiber Discrimination

Abstract: The potential of total excitation-emission fluorescence microscopy combined with multiway chemometric analysis was investigated for the nondestructive forensic analysis of textile fibers. The four pairs of visually indistinguishable fibers consisted of nylon 361 dyed with acid yellow 17 and acid yellow 23, acetate satin 105B dyed with disperse blue 3 and disperse blue 14, polyester 777 dyed with disperse red 1 and disperse red 19, and acrylic 864 dyed with basic green 1 and basic green 4. Excitation emission m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…processes, storage, harvest or variety). Other relevant works have been orientated to more specific research, such as the forensic analysis of textile fibers [40,41], the characterization of organic constituents of soils [42], discrimination of geographical origin and detection of adulteration of burdook and kudzu roots [43,44], and for the identification of biodiesel and petroleum oils with environmental purposes [7,45,46]. Several recent reviews have been published about this ever increasing research field where relevant applications can be found [47][48][49][50][51][52][53].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…processes, storage, harvest or variety). Other relevant works have been orientated to more specific research, such as the forensic analysis of textile fibers [40,41], the characterization of organic constituents of soils [42], discrimination of geographical origin and detection of adulteration of burdook and kudzu roots [43,44], and for the identification of biodiesel and petroleum oils with environmental purposes [7,45,46]. Several recent reviews have been published about this ever increasing research field where relevant applications can be found [47][48][49][50][51][52][53].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Accordingly, the simplest implemented strategies, when the affected areas do not contain relevant information, are reducing the areas of analysis, previously to the measurements, selecting the wavelength range from which the scattering effects are not produced [40,41]. However, important information about some sample fluorophores can be lost [41].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, single ber identication with nondestructive excitation-emission uorescence spectroscopy combined with different chemometric techniques has been reported by our group. [9][10][11] This subject is of current interest, as is reported in a recent review on forensic comparison of synthetic bers. 12 Our approach takes room temperature uorescence (RTF) spectroscopy to a higher level of selectivity.…”
Section: Introductionmentioning
confidence: 99%